A method for synergistically improving the strength and plasticity of laser-added titanium alloy
By adding nanoscale ceramic powder to laser-added titanium alloy and performing a rolling process, the problem of coarse α lath structure and insufficient density in the titanium alloy structure is solved, and the strength and plasticity of the material are significantly improved.
Patent Information
- Application Number
- CN202211575143.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-12-08
AI Technical Summary
The α-slat structure in the laser additive titanium alloy is relatively thick and the structure cannot be completely dense, which greatly affects the strong plastic properties of the laser additive titanium alloy.
Nanoscale ceramic powder is added to titanium alloy powder, and laser powder deposition technology is used for additive preparation, followed by a rolling process to refine the size of the α phase and improve the density of the additive structure.
By refining the size of the α phase and increasing the density of the additive structure, the strength and plasticity of laser-added titanium alloys are significantly improved, achieving simultaneous improvement in strong plasticity.
Smart Images

Figure CN115740489B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laser additive manufacturing, and in particular to a method for synergistically improving the strength and plasticity of laser additively manufactured titanium alloy. Background Art
[0002] Titanium alloy has high specific strength, specific modulus and excellent fatigue resistance, corrosion resistance, heat resistance and biocompatibility. It is currently the most popular structural functional material and biomedical material, and is widely used in aerospace, military, medical, shipbuilding and civil equipment fields.
[0003] Laser additive manufacturing is an advanced manufacturing technology that combines laser cladding technology with rapid prototyping technology. This technology uses high-energy laser beams as heat sources and powder / wire feeding or powder laying as material supply methods. It achieves rapid prototyping of three-dimensional solid parts through layered processing and layer-by-layer accumulation, effectively shortening the production cycle and reducing part processing costs. In addition, laser additive manufacturing can also achieve rapid repair of worn parts.
[0004] Compared with traditional processing methods, laser additive manufacturing can perform near-net shaping of materials, and the production process does not require molds, which greatly reduces the production cycle and production costs. However, in the laser additive titanium alloy structure, the α lath structure is relatively coarse and the structure cannot be completely dense, which greatly affects the strength and plasticity of the laser additive titanium alloy.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for synergistically improving the strength and plasticity of laser-added titanium alloy, so as to improve the problem in the prior art that the α lath structure in the laser-added titanium alloy is relatively coarse and the structure cannot be completely dense, which greatly affects the strength and plasticity of the laser-added titanium alloy.
[0007] The present invention is achieved in that:
[0008] A method for synergistically improving the strength and plasticity of laser-added titanium alloy, the steps of which include: using laser powder deposition technology to perform additive preparation on mixed powder; and then rolling the alloy after additive preparation to obtain a titanium alloy part;
[0009] The mixed powder comprises titanium alloy powder and nano-grade ceramic powder.
[0010] In an optional embodiment, the titanium alloy powder is spherical particles, and the particle diameter of the titanium alloy powder is in the range of 50-200 μm.
[0011] In an optional embodiment, the ceramic powder is selected from at least one of Y2O3 powder and ZrO2 powder.
[0012] In an optional embodiment, the ceramic powder is spherical particles, and the particle diameter of the ceramic powder is in the range of 1-100 nm.
[0013] In an optional embodiment, the added amount of the ceramic powder is 0.1%-1% of the mass of the mixed powder.
[0014] In an optional embodiment, the method of preparing the titanium alloy powder and the ceramic powder into a mixed powder includes ball milling.
[0015] In an optional embodiment, the ball-to-material ratio of the ball-milled mixed powder is 2-3:1.
[0016] In an optional embodiment, argon is used as a protective gas during the ball milling mixing process.
[0017] In an optional embodiment, the rotation speed of the ball milling powder mixing is 300-500r / min.
[0018] In an optional embodiment, the ball milling mixing time is 300-360 minutes.
[0019] In an optional embodiment, the mixed powder is dried by vacuum heating, the vacuum heating temperature is 80-100° C., and the vacuum heating time is 300-360 min.
[0020] In an optional embodiment, before the additive manufacturing is performed, the surface of the titanium alloy substrate is polished, cleaned and dried.
[0021] In an optional embodiment, the thickness of the titanium alloy substrate is 20-50 mm.
[0022] In an optional embodiment, the cleaning solution used in the cleaning step is acetone and / or alcohol.
[0023] In an optional embodiment, the laser powder deposition technology includes: placing the mixed powder in a powder feeder and fixing the titanium alloy substrate on an additive workbench; setting the parameters of laser additive; controlling the powder feeding head of the powder feeder to be located above the substrate and the laser focus emitted by the laser head to be located on the surface of the substrate; and running the laser additive program.
[0024] In an alternative embodiment, additive manufacturing is performed in a chamber containing an inert gas.
[0025] In an alternative embodiment, the inert gas comprises argon and the oxygen content in the chamber is 0-5 ppm.
[0026] In an optional embodiment, the parameters of laser additive include: the rotation speed of the powder feeder is 5-20r / min, the powder blowing in the powder feeder is argon, and the gas flow rate is 10-25L / min; the laser power is 600-2000W, the laser head movement rate is 300-2000mm / min, and the deposition layer height is 0.3-0.6mm.
[0027] In an optional embodiment, the diameter of the laser spot at the laser focus is 1.0-3.0 mm.
[0028] In an optional embodiment, the rolling force in the rolling step is 5-20 kN.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention adds nano-scale ceramic powder to titanium alloy powder and cooperates with the rolling process to provide a nucleating agent for the transformation of high-temperature β phase to low-temperature α phase of titanium alloy, refine the size of α phase, and improve the density of additive structure. The nanoparticles in the structure can also improve the strength of the alloy, thereby achieving a simultaneous improvement in the strength and plasticity of laser additive titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 The mixed powder laser additive deposited structure in Example 1;
[0033] Figure 2 The mixed powder laser additive deposition structure in Example 2;
[0034] Figure 3 This is the laser additive deposition structure in Comparative Example 1;
[0035] Figure 4 The mechanical properties test results of the mixed powder laser additive structure in Example 1 and Comparative Example 1;
[0036] Figure 5 The mechanical properties test results of the mixed powder laser additive structure in Example 2 and Comparative Example 2;
[0037] Figure 6 These are the mechanical properties test results of the laser-additive structures in Comparative Examples 3 and 4. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] In the prior art, the α lath structure in the laser additive titanium alloy is relatively coarse and the structure cannot be completely dense, which greatly affects the strength and plasticity of the laser additive titanium alloy. In order to improve the above technical problems, the inventors of the present invention have improved the mixed powder raw materials of laser additive on the basis of the prior art, and adopted a rolling process to roll the additive alloy to refine the microstructure and improve the density of the material, thereby improving the strength and plasticity of the laser additive titanium alloy.
[0040] Based on this, the present invention provides a method for synergistically improving the strength and plasticity of laser-added titanium alloy, the steps of which include: adding nano-ceramic powder to titanium alloy powder, mixing evenly and drying for later use; using laser powder deposition technology to perform additive preparation on the mixed powder; and then rolling the alloy after additive preparation to obtain titanium alloy parts.
[0041] Specifically, the above method for synergistically improving the strength and plasticity of laser-added titanium alloy includes the following steps:
[0042] (1) A certain amount of nano-scale ceramic powder is added to the titanium alloy powder, and the powder is mixed evenly by a ball milling method. The evenly mixed powder is placed in a vacuum heating furnace for drying and set aside; the surface of the titanium alloy substrate is polished, cleaned and blown dry for set aside.
[0043] It should be noted that the powder mixing method here is not limited to ball milling, and other mixing methods can also be used.
[0044] In some embodiments, the titanium alloy powder includes TC4 alloy powder, but is not limited to TC4 alloy powder, and may also be other dual-phase titanium alloy powder.
[0045] In some embodiments, the titanium alloy powder is a spherical particle powder, and the particle diameter thereof is in the range of 50-200 μm.
[0046] Optionally, the particle diameter range of the titanium alloy powder is 50-200μm, the particle diameter range of the titanium alloy powder is 50-150μm, the particle diameter range of the titanium alloy powder is 50-100μm, the particle diameter range of the titanium alloy powder is 100-150μm, the particle diameter range of the titanium alloy powder is 100-200μm, or the particle diameter range of the titanium alloy powder is 150-200μm.
[0047] In some embodiments, the nano-scale ceramic powder is selected from at least one of Y2O3 powder or ZrO2 powder.
[0048] In the present invention, the Y2O3 powder or ZrO2 powder in the mixed powder can be used as a nucleating agent in the process of the high-temperature β phase to the low-temperature α phase of the titanium alloy, refine the size of the α phase, and improve the density of the additive structure. In addition, the addition of nanoparticles in the structure can also improve the strength of the alloy, achieving a simultaneous improvement in the strength and plasticity of the laser additive titanium alloy.
[0049] In some embodiments, the ceramic powder is in the form of spherical particles, and the particle diameter of the ceramic powder is in the range of 1-100 nm.
[0050] The present invention uses finer nano-ceramic particles, which can help assist the nucleation process and obtain finer microstructures. In addition, finer nano-particles also help improve strength and toughness.
[0051] Optionally, the particle diameter of the ceramic powder is in the range of 1-100 nm, the particle diameter of the ceramic powder is in the range of 1-50 nm, or the particle diameter of the ceramic powder is in the range of 50-100 nm.
[0052] In some embodiments, the amount of ceramic powder added is 0.1%-1% of the mass of the mixed powder.
[0053] The titanium alloy parts prepared by using the above addition amount have better performance. When the addition amount is less than 0.1%, the effect is not obvious. When the addition amount is greater than 1%, the structure becomes brittle and the toughness is reduced.
[0054] Optionally, the mass percentage of the ceramic powder to the titanium alloy mixed powder may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%, or any value between 0.1% and 1%.
[0055] In some embodiments, when the powder is mixed by ball milling, the ball milling tank is filled with an inert gas, which may be argon.
[0056] In some embodiments, the ball-to-material ratio during the ball milling process is 2-3: 1. The ball milling medium in the present invention can be agate beads or steel balls, or other conventional ball milling media.
[0057] Optionally, the ball-to-material ratio may be 2:1, 2.5:1 or 3:1, or any ratio between 2-3:1.
[0058] In some embodiments, during the ball milling process, the rotation speed of the ball mill is 300-500 r / min, and the ball milling time is 300-360 min.
[0059] Optionally, the rotation speed of the ball mill can be 300r / min, 400r / min or 500r / min, or any value between 300-500r / min; the ball milling time can be 300min, 310min, 320min, 330min, 340min, 350min or 360min, or any value between 300-360min.
[0060] The mixed powder is dried by vacuum heating, the vacuum heating temperature is 80-100° C., and the vacuum heating time is 300-360 minutes.
[0061] Optionally, the vacuum heating temperature can be 80°C, 90°C or 100°C, or any value between 80-100°C; the vacuum heating time can be 300min, 310min, 320min, 330min, 340min, 350min or 360min, or any value between 300-360min.
[0062] In some embodiments, acetone and / or alcohol are used to clean the titanium alloy substrate.
[0063] (2) Laser powder deposition technology is used to perform additive manufacturing on titanium alloy. The machine tool and the laser powder feeding head are completely placed in an inert atmosphere chamber filled with argon gas, and the powder is delivered to the laser focus position inside the chamber through the powder feeder.
[0064] (3) Add the mixed powder into the powder feeder, place the titanium alloy substrate on the additive workbench, and fix the substrate with screws. Close the sealed chamber door and fill the chamber with inert gas. Set relevant parameters, including powder feeder speed, powder blowing flow, laser power, laser head movement rate, layer height, deposition width, number of deposition layers, etc.
[0065] In some embodiments, the additive manufacturing of titanium alloy is carried out in an inert atmosphere chamber filled with argon, wherein the inert gas is generally argon, and the oxygen content of the chamber is 0-5 ppm after the chamber is filled with the inert gas.
[0066] In some embodiments, the powder feeder rotates at a speed of 5-20 r / min.
[0067] Optionally, the powder feeder rotation speed may be 5 r / min, 10 r / min, 15 r / min or 20 r / min, or any value between 5-20 r / min.
[0068] In some embodiments, the powder blowing gas is argon gas, and the gas flow rate of the powder blowing gas is 10-25 L / min.
[0069] Optionally, the gas flow rate may be 10 L / min, 15 L / min, 20 L / min or 25 L / min, or any value between 10-25 L / min.
[0070] In some embodiments, the laser power is 600-2000W.
[0071] Optionally, the laser power may be 600W, 800W, 1000W, 1200W, 1400W, 1600W, 1800W or 2000W, or any value between 600-2000W.
[0072] In some embodiments, the laser head movement rate is 300-2000 mm / min.
[0073] Optionally, the movement rate of the laser head may be 300 mm / min, 400 mm / min, 800 mm / min, 1500 mm / min or 2000 mm / min, or any value between 300-2000 mm / min.
[0074] In some embodiments, the deposited layer height is 0.3-0.6 mm.
[0075] Optionally, the deposition layer height may be 0.3 mm, 0.4 mm, 0.5 mm or 0.6 mm, or any value between 0.3-0.6 mm.
[0076] It should be noted that the width of the deposition and the number of deposition layers need to be set according to the actual size of the titanium alloy component, and the present invention does not make specific limitations here.
[0077] (4) Move the laser powder feeding head to a suitable position above the substrate and ensure that the laser focus is on the plane of the plate. Run the laser deposition additive program to perform additive preparation on the titanium alloy.
[0078] In some embodiments, the energy distribution of the laser beam is uniform, and the diameter of the laser spot at the laser focus is 1.0-3.0 mm.
[0079] (5) Setting the rolling force and rolling the alloy after material addition to obtain the final alloy.
[0080] In some embodiments, the rolling force is 5-20 kN.
[0081] When the rolling force is less than 5kN, the deformation of the sample is small and the improvement in strength and toughness is limited; when the rolling force is greater than 20kN, the sample is prone to cracking during the rolling process.
[0082] Optionally, the rolling force may be 5 kN, 10 kN, 15 kN or 20 kN, or any value between 5 and 20 kN.
[0083] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0084] Example 1
[0085] This embodiment provides a method for synergistically improving the strength and plasticity of laser-added titanium alloy, which mainly includes the following steps:
[0086] S1. Add Y2O3 powder into TC4 powder, wherein the Y2O3 powder is a nano-scale spherical powder with an average diameter of 50 nm and a mass fraction of 0.5%, and the rest is TC4 titanium alloy powder with spherical particles and a diameter range of 53-150 μm.
[0087] S2. Use a ball mill to mix the powders, with a ball-to-material ratio of 3:1, the ball mill is filled with argon, the speed is 500r / min, and the ball milling time is 300min. After the ball milling is completed, the powders are placed in a vacuum heating furnace, the temperature is set to 100℃, and the insulation time is 360min.
[0088] S3. Use a titanium alloy with a size of 100 mm × 200 mm × 30 mm as an additive substrate, use a grinder to remove the oxide film on the surface of the titanium alloy, and clean the plate with acetone and alcohol and then blow dry.
[0089] S4. A semiconductor laser additive system is used for laser additive deposition of titanium alloy. The laser powder feeding system is placed in a closed chamber, the beam energy is evenly distributed, and the spot diameter at the focus is 2.0 mm.
[0090] S5. Add powder to the powder feeder, place the titanium alloy substrate on the additive workbench, and fix the substrate with screws. Close the sealed chamber door, and use Ar gas to exhaust the air inside the chamber, and keep the oxygen content at 1-3ppm.
[0091] S6. The powder feeder speed is set to 15r / min, the powder blowing Ar gas flow rate is set to 15L / min, the laser power is set to 1200W, the laser head movement rate is set to 800mm / min, the layer height is set to 0.5mm, the deposition width is set to 150mm, and the number of deposition layers is set to 300 layers.
[0092] S7. Turn on the laser guide spot, adjust the laser beam position to the edge of the plate, and adjust the beam focus to the surface of the titanium alloy substrate.
[0093] S8. Run the program to start the titanium alloy mixed powder laser additive process.
[0094] S9. After the additive manufacturing is completed, the obtained alloy is taken out and rolled, and the rolling force is set to 15 kN.
[0095] Example 2
[0096] This embodiment provides a method for synergistically improving the strength and plasticity of laser-added titanium alloy, which mainly includes the following steps:
[0097] S1. Add ZrO2 powder into TC4 powder, wherein the ZrO2 powder is a nano-scale spherical powder with an average particle diameter of 50 nm and a mass fraction of 0.5%, and the rest is TC4 titanium alloy powder with spherical particles and a particle diameter range of 53-150 μm.
[0098] S2. Use a ball mill to mix the powders, with a ball-to-material ratio of 3:1, the ball mill is filled with argon, the speed is 500r / min, and the ball milling time is 300min. After the ball milling is completed, the powders are placed in a vacuum heating furnace, the temperature is set to 100℃, and the insulation time is 360min.
[0099] S3. Use a titanium alloy with a size of 100 mm × 200 mm × 30 mm as an additive substrate, use a grinder to remove the oxide film on the surface of the titanium alloy, and clean the plate with acetone and alcohol and then blow dry.
[0100] S4. A semiconductor laser additive system is used for laser additive deposition of titanium alloy. The laser powder feeding system is placed in a closed chamber, the beam energy is evenly distributed, and the spot diameter at the focus is 2.0 mm.
[0101] S5. Add powder to the powder feeder, place the titanium alloy substrate on the additive workbench, and fix the substrate with screws. Close the sealed chamber door, and use Ar gas to exhaust the air inside the chamber, and keep the oxygen content at 1-3ppm.
[0102] S6. The powder feeder speed is set to 15r / min, the powder blowing Ar gas flow rate is set to 15L / min, the laser power is set to 1200W, the laser head movement rate is set to 800mm / min, the layer height is set to 0.5mm, the deposition width is set to 150mm, and the number of deposition layers is set to 300 layers.
[0103] S7. Turn on the laser guide spot, adjust the laser beam position to the edge of the plate, and adjust the beam focus to the surface of the titanium alloy substrate.
[0104] S8. Run the program to start the titanium alloy mixed powder laser additive process.
[0105] S9. After the additive manufacturing is completed, the obtained alloy is taken out and rolled, and the rolling force is set to 15 kN.
[0106] Comparative Example 1
[0107] The difference between this comparative example and Example 1 is that the rolling step is not performed after the additive manufacturing is completed, and the other steps are the same as those in Example 1.
[0108] Comparative Example 2
[0109] The difference between this comparative example and Example 2 is that the rolling step is not performed after the additive manufacturing is completed, and the other steps are the same as those in Example 2.
[0110] Comparative Example 3
[0111] The difference between this comparative example and Example 1 and Example 2 is that no nano-sized Y2O3 powder or ZrO2 powder is added, and the other steps are the same as those of Example 1 and Example 2.
[0112] Comparative Example 4
[0113] The difference between this comparative example and Example 1 and Example 2 is that neither nano-scale Y2O3 powder or ZrO2 powder is added, and no rolling step is performed after the additive manufacturing is completed. The other steps are the same as those of Example 1 and Example 2.
[0114] Experimental example
[0115] The α phase of the titanium alloy parts prepared in Examples 1-2 and Comparative Example 3 was observed, and the tensile strength of the titanium alloy parts prepared in Examples 1-2 and Comparative Example 1-4 was tested.
[0116] The laser additive deposited structures of Examples 1-2 and Comparative Example 3 are as follows: Figure 1-3 By comparison Figure 1-3 The α laths inside the grains under different conditions are shown. It is found that after adding nano-scale Y2O3 powder, the lath size is reduced, while after adding nano-scale ZrO2 powder, the α laths become smaller.
[0117] The tensile strength test results of the laser-added structures in Example 1 and Comparative Example 1 are as follows: Figure 4 As shown, the tensile strength test results of the laser-added structures in Example 2 and Comparative Example 2 are as follows Figure 5 As shown, the tensile strength test results of the laser-added structures in Comparative Examples 3 and 4 are as follows Figure 6 As shown. Figure 4-6By comparison, it was found that under different compositions, the strength and plasticity of the material could not be significantly improved by simply adding nano-scale Y2O3 powder or ZrO2 powder. By comparing the same composition with and without rolling, it was found that the strength and plasticity of the material were greatly improved under the rolling process. By comparing the rolling performance of materials with the addition of nano-scale Y2O3 powder or ZrO2 powder with the performance of the original materials without addition and rolling, it was found that their strength and toughness were greatly improved, especially the rolling performance of materials with the addition of nano-scale ZrO2 powder. Compared with the original TC4, the strength was increased by 41% and the elongation was increased by 216%.
[0118] In summary, the use of nano-particle Y2O3 powder or ZrO2 powder combined with the rolling process can significantly improve the strength and toughness of laser-added titanium alloy tissue.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for synergistically improving the strength and plasticity of laser-added titanium alloy, characterized in that: The steps include: using laser powder deposition technology to perform additive preparation on the mixed powder; then rolling the alloy after additive preparation to obtain a titanium alloy part; The mixed powder is titanium alloy powder and nano-grade ceramic powder, the ceramic powder is selected from at least one of Y2O3 powder and ZrO2 powder, and the added amount of the ceramic powder is 0.1%-1% of the mass of the mixed powder.
2. The method according to claim 1, characterized in that The titanium alloy powder is spherical particles, and the particle diameter of the titanium alloy powder ranges from 50 to 200 μm.
3. The method according to claim 1, characterized in that The ceramic powder is spherical particles, and the particle diameter of the ceramic powder is in the range of 1-100 nm.
4. The method according to claim 1, characterized in that: The method of preparing the titanium alloy powder and the ceramic powder into the mixed powder includes ball milling.
5. The method according to claim 4, characterized in that The ball-to-material ratio of the ball-milled mixed powder is 2-3:
1.
6. The method according to claim 5, characterized in that Argon is used as protective gas during the ball milling powder mixing process.
7. The method according to claim 6, characterized in that The rotation speed of the ball mill powder mixing is 300-500r / min.
8. The method according to claim 7, characterized in that The ball milling mixing time is 300-360 minutes.
9. The method according to claim 1, characterized in that: The mixed powder is dried by vacuum heating, the vacuum heating temperature is 80-100° C., and the vacuum heating time is 300-360 minutes.
10. The method according to claim 1, characterized in that Before additive manufacturing, the surface of the titanium alloy substrate is also polished, cleaned and dried.
11. The method according to claim 10, characterized in that The thickness of the titanium alloy substrate is 20-50 mm.
12. The method according to claim 11, characterized in that The cleaning solution used in the cleaning step is acetone and / or alcohol.
13. The method according to claim 12, characterized in that The laser powder deposition technology includes: placing the mixed powder in a powder feeder and fixing the titanium alloy substrate on an additive workbench; setting parameters for laser additive; controlling the powder feeding head of the powder feeder to be located above the substrate and the laser focus emitted by the laser head to be located on the surface of the substrate; and running the laser additive program.
14. The method according to claim 13, characterized in that The additive preparation is carried out in a chamber containing an inert gas.
15. The method according to claim 14, characterized in that The inert gas includes argon, and the oxygen content in the chamber is 0-5 ppm.
16. The method according to claim 15, characterized in that The parameters of the laser additive include: the rotation speed of the powder feeder is 5-20r / min, the powder blowing gas in the powder feeder is argon gas, and the gas flow rate is 10-25L / min; the laser power is 600-2000W, the laser head movement rate is 300-2000mm / min, and the deposition layer height is 0.3-0.6mm.
17. The method according to claim 16, characterized in that The diameter of the laser spot at the laser focus is 1.0-3.0 mm.
18. The method according to claim 1, characterized in that The rolling force in the rolling step is 5-20 kN.
Citation Information
Patent Citations
Preparation method of hierarchically-structured composite material with nano-ceramic particle reinforced metal matrix
CN109852834A
Titanium alloy mixed powder for preparing titanium alloy part through laser additive and method for preparing titanium alloy part through laser additive mode
CN113967734A